THE ENHANCEMENT OF GIVING REASONS AND IDENTIFYING CONCLUSIONS SKILLS IN SOLUBILITY AND SOLUBILITY PRODUCT CONCEPT BY PROBLEM SOLVING LEARNING MODEL - novitasari novitasari; noor fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is to describe the effectiveness of problem solving learning model in solubility and solubility product concept to enhance giving reason and identifying conclusion skills.  Students who became the subject of this research was  XI grade of Science 1 Batanghari Senior High School in Batanghari Academic Year 2011/2012.  This research used the pre-experimental method and one group pretest-posttest design. The effectiveness of problem solving learning model was determined based on the average value of n-Gain.  The results of this research showed that the average value of n-Gain of giving reason and identifying conclusion skills were 0,39 and 0,72.  Thus, it can be concluded that the problem solvinglearning model in solubility and solubility product concept effective to enhance giving reason skill in medium category and effective to enhance identifying conclusion skill ept in high category.Keywords: problem solving learning, giving reasons skill, and identifying                    conclusions skill.